Some T 2 Terrace Soils of Peninsular Malaysia: III. Surface Charge Properties* - Jusop, Shamsuddin; Tessens, Eddy (1985)
The charge properties of 8 sod series were studied. The study shows that gibbsite is related to the pH0 of these soils. Negative charges exceed positive charges at the pH range of 3 to 6, thus the PZNC of these soils cannot be obtained. The sum of A l and bases is a better estimate of ECEC than of the PC of the soils. These soils are either in the recent or intermediate stage of weathering, shown by the low pH0 and high weathering index.